Thermal and spectroscopy investigation of cyclopalladated compounds of the type [Pd(C(1)3H(1)0N)(mu-X)](2), (X=H3CCOO, NCO, SCN, CN) - Santana, A. M.; Mauro, A. E.; Zorel, H. E.; Mattioli, MPD; Neto, VAD (Kluwer Academic Publ, 2002)
The dimeric compound [Pd(bzan)(mu-OOCCH3)](2) (1) (bzan=N-benzylideneaniline) reacts with KX, in methanol/acetone (2:1), affording the analogous dimeric pseudohalogen-bridged species [Pd(bzan)(mu-X)](2) [X=NCO(2), SCN(3), CN(4)]. The compounds were characterized by elemental analysis, infrared spectroscopy, NMR and thermogravimetric analysis. IR data for 2-4 showed bands typical of coordinated pseudohalogen ligands clearly indicating the occurrence of the exchange reaction. Their thermal behaviour was investigated and suggested that their stability is influenced by the bridging ligand. The thermal stability decreased in the order [Pd(bzan)(mu-CN)](2)>[Pd(bzan)(mu-SCN)](2)>[Pd(bzan)(mu-OOCCH3)](2)>[Pd(bzan)(mu-NCO)](2). X-ray results showed the formation of Pddegrees as final decomposition product.
Keywords: cyclopalladated; IR spectroscopy; pseudohalogens; thermal analysis; X-ray diffraction